Pelatihan Pengembangan Mikroskop Digital sebagai Media Pembelajaran di SMAN 3 Kefamenanu - Wiguna, Gede Arya; Kamaluddin, Kamaluddin; Prima R Makin, Florian Mayesti; Welsiliana, Welsiliana; Hanas, Dicky Frengky; Paramita, Dira Asri (Lembaga Dongan Dosen, 2023)
A microscope is a very important tool in learning biology. The preparation media cannot be used optimally if it is not supported by a microscope. Technological developments have succeeded in changing ordinary light microscopes into digital ones. Adding a camera to a microscope and installing software on a computer becomes an effective and efficient biology learning medium. This activity aims to provide training to teachers and students regarding the development of digital microscopes as learning media at SMAN 3 Kefamenanu. The methods used in this service activity include lectures, direct observation practice and group discussions. The results obtained from this activity are that teachers and students gain knowledge about digital microscopes and preparations, are able to operate digital microscopes and make fresh preparations independently. The evaluation results showed that 85% of participants were very satisfied with the service activities that had been carried out. Training on developing digital microscopes as a learning medium at SMAN 3 Kefamenanu can have a positive influence. Teachers and students are greatly helped in practicum-based biology learning activities. Practical activities can take place effectively and efficiently. Apart from that, teachers and students also gain knowledge and experience regarding digital microscopes, operating digital microscopes, calibration, and making fresh preparations.